REMEDIBERBANTUANKOMPUTERSEBAGAIUPAYA UNTUK MENINGKATKAN PRESTASI BELAJAR FISlKA ZAT PADAT - Istiyono, Edi (Jurnal Cakrawala Pendidikan, 2016)
The objective ofresearch were: (I) to determine the influence of remedial program by computer on the achievement of the Solid State Physics and (2) to determine the students self-learning in the remedial program by computer. Subject of research was the student of the Study Program of Physics of Mathematics and Science Faculty in Yogyakarta- State University who took the Solid State Physics Subject. Data were gathered by meant of: (1) test and (2) observation. Test was used to collect the students achievement in the Solid State Physics. By analyzing of data, it was concluded that: (1) remedial program by computer increases the learning achievement of the Solid State Physics and (2) the most of students are self-learning in the remedial program by computer